Conflict antiquities' rescue or ransom: The cost of buying back stolen cultural property in contexts of political violence. Issue 1 (18th February 2021) - Hardy, Samuel Andrew
Abstract: Rescue has long been a defense for the removal of cultural property. Since the explosion of iconoclasm in West Asia, North Africa, and West Africa, there has been a growing demand for cultural property in danger zones to be "rescued" by being purchased and given "asylum" in "safe zones" (typically, in the market countries of Western Europe and North America). This article reviews evidence from natural experiments with the "rescue" of looted antiquities and stolen artifacts from across Asia and Europe. Unsurprisingly, the evidence reaffirms that "rescue" incentivizes looting, smuggling, and corruption, as well as forgery, and the accompanying destruction of knowledge. More significantly, "rescue" facilitates the laundering of "ordinary" illicit assets and may contribute to revenue streams of criminal organizations and violent political organizations; it may even weaken international support for insecure democracies. Ultimately, "rescue" by purchase appears incoherent, counter-productive, and dangerous for the victimized communities that it purports to support.